Assessment of depression, anxiety, and social support in the context of therapeutic abortion. Issue 4 (20th April 2019) - Akdag Topal, Cansu; Terzioglu, Fusun
Abstract: Purpose: The purpose of this study is to determine the levels of anxiety, depression, social support, and nursing care needed by women undergoing therapeutic abortion. Designs and Methods: Sixty women were administered a sociodemographic form, the Hospital Anxiety Depression Scale and the Multidimensional Perceived Social Support Scale. Results: More than half of the women experienced anxiety (61.7%). Anxiety scores were high (10.8 ± 3.7), and most of the women had depression (85.0%). Social support from family and friends of the women decreased the women's anxiety and depression levels significantly; social support from their partners also decreased the women's anxiety levels ( P < 0.05). Practice Implications: Support from family and friends after therapeutic abortion is a fundamental affective variable on anxiety scores.